Partial orthotopic liver transplantation in combination with two-stage hepatectomy: A proof-of-concept explained by mathematical modeling. (March 2020) - Golse, Nicolas; Joly, Florian; Nicolas, Quentin; Vibert, Eric; Line, Pal Dag; Clementel, Irene Vignon
Abstract: Background: R esection A nd P arti al Liver Segment 2/3 Transplantation with D elayed total hepatectomy (RAPID) includes total hepatectomy in 2 steps with small graft transplantation at first stage. To avoid graft portal hyperperfusion, portal vein pressure monitoring is required after revascularization and right portal vein clamping. To date, portal flow modulation has not been reported but simulating hemodynamics in RAPID patients would be useful to anticipate these procedures. Our team developed hemodynamic 0D modeling; we aimed to assess if this mathematical model could be accurately used in the RAPID setting. Methods: The modified 0D model was retrospectively tested on 3 patients. We compared our estimated portal vein pressures and portocaval gradients to those intraoperatively measured, as indication to modulate portal flow relies on these measures. Findings: Portal pressures measured after right portal vein clamping (end of RAPID procedure) in patients 1, 2 and 3 were respectively of 14, 16 and 12 mmHg while the simulated pressures were of 13.1, 14.8 and 11.5 mmHg ( p  = 0.25). Portocaval gradients measured after right portal vein clamping in the 3 patients were respectively of 10, 11 and 7 mmHg while the simulated gradients were of 9.9, 11.6 and 8.3 mmHg ( p  = 0.5). Interpretation: We succeeded to predict portal vein pressures and portocaval gradients after RAPID. This promising report demonstrates that 0D simulation could be a useful tool for human decision-making. Moreover, such a patient-specific model could be of importance if we transpose RAPID experience to hepatocellular carcinoma bearing cirrhotics, a population with high probability of portal hypertension after RAPID. Highlights: Partial liver transplantation with two-stage hepatectomy is an innovative procedure. This procedure is at high-risk of portal hypertension (small for size syndrome). 0D modeling is able to simulate intraoperative hemodynamic evolution. Surgical planning may be facilitated by mathematical models. Numerical model may improve the access to liver grafts.